Fibre insert mould for injection moulding - Norjamalullail Tamri,; Rozli Zulkifli,; Che Husna Azharia,; Ude, Albert Uchenna (Penerbit Universiti Kebangsaan Malaysia, 2020)
Insert moulding is equivalent to over-moulding. Both processes are achieved by inserting different materials into one another in the same mould to improve product’s capability. This process will increase the value of a resulting product because of the additional material price, material insertion process and cycle time. Such moulding process directly increases the overall price of a product but the price is cheaper compared with that of other processes or materials that have the same shape and strength. This insert moulding process requires two moulding materials. The first material is coated by the injected material, which then becomes solid and hardens to cover the second material. In general, the second material is placed permanently in the mould section. When the mould is closed, the injection moulding process is performed. The parts placed in the mould are made of metal, which will attach and reinforce the product. Dumbbell-ready injection is released along with kenaf yarn content in the middle, which is called the fibre insert mould. The fibre insertion technique is conducted by finding the problem of fibre. Then, the small fibre is cut while inside the barrel (either through moulding or compounding). Yarn-shaped fibres are placed on the core of a mould and clamped. Subsequently, a plastic material is injected into the mould. Consequently, the tensile strength of polypropylene (PP) will increase by 55%. A cheaper material (kenaf yarn) can increase the strength of the PP through an easier and cheaper process. The number of processes is reduced from three (before: cutting > compounding > moulding then finished) to two (after: insert and moulding then finished).